What does it mean to provide process-oriented training? - Bahl, Anke [Verfasser]; Koch, Johannes [Verfasser]; Meerten, Egon [Verfasser]; Zinke, Gert [Verfasser] (My University, 2007)
"The new training regulations stipulate the demand for "process-oriented" implementation of training, with the goal of simplifying the adaptation of training to the requirements of industrial work processes and the rapid technological and organisational transformations. The current regulations specify business tasks which are described in general terms, and the enterprises have to provide the clear definition of the content themselves. This article describes the consequences for the implementation of training which arise from process orientation and designates the new tasks connected with it and the skills requirements for the personnel involved." (BIBB)
Erstveröffentlichung der englischen Version des Artikels in: BWP Special Edition 2005, S. 27-31
Keywords: L 1.1.2 Handlungs- und Lernfeldorientierung; L 1.2.2 Betriebliche Ausbildungsorganisation; L 1.2.3 Schulische Ausbildungsorganisation; Prozessorientierung; Ausbildungsordnung; Lernorganisation; Betriebliche Berufsausbildung; Ausbilder; Weiterbildungsbedarf